Evaluation of RV-arterial coupling in advanced heart failure. (4th February 2022) - Dias Ferreira Reis, JP; Bras, P; Ferreira, V; Goncalves, A; Pereira Da Silva, T; Soares, R; Timoteo, AT; Galrinho, A; Branco, L; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The ratio of echocardiography-derived tricuspid annular plane systolic excursion (TAPSE) and pulmonary arterial systolic pressure (PASP) - TAPSE/PASP ratio - is a noninvasive measure of RV-arterial coupling. TAPSE/PASP ratio is a potent independent predictor of prognosis in heart failure and pulmonary arterial hypertension, with a prognostic cutoff value of 0.36 mm/mmHg. Objective: To assess the prognostic impact of TAPSE/PASP ratio in a population of advanced HF patients. Methods: Prospective evaluation of adult patients with advanced HFrEF referred to our Institution for evaluation with HF team and possible indication for urgent heart transplantation (HT) or MCS. Patients were followed up for 2 years for the primary endpoint of cardiac death and HT. Echocardiographically determined TAPSE/PASP ratio was used to assess RV-arterial coupling and a survival analysis was performed to evaluate the prognostic impact of the suggested cutoff of 0.36 mm/mmHg. Results: A total of 450 Heart Failure with Reduced Ejection Fraction (HFrEF) patients with a mean age of 56 ± 12 years, of which 80% are male, and with a mean LVEF of 29 ± 4%, mean TAPSE of 19 ± 3 mm and PASP of 38 ± 11mmHg. The mean TAPSE/PASP was 0.80 ± 0.28. Fifty-four patients (12%) met the primary endpoint. Patients with RV-arterial uncoupling (TAPSE/PASP < 0.36 mm/mmHg) were more likely to have a non-ischaemic etiology for HF (66.7% vs 40%, p = 0.047), had a lower prevalence of diabetes (53.3% vs 77.9%, p = 0.041), a higher prevalence of moderate-to-severe mitral regurgitation (33.3% vs 13.0%, p = 0.035), a lower LVEF (26.2 ± 6.1 vs 29.9 ± 5.9, p = 0.038), a higher prevalence of RV dysfunction (73.3% vs 26.7%, p < 0.001) and worse cardiopulmonary fitness (pVO2: 12.7 ± 5.1 vs 15.8 ± 6.0 ml/kg/min, p = 0.047; VE/VCO2 slope: 49.5 ± 17.2 vs 37.6 ± 9.7, p < 0.001; cardiorespiratory optimal point: 36.9 ± 11.3 vs 29.0 ± 6.4, p < 0.001). More patients in the group of TAPSE/PASP < 0.36 mm/mmHg met the primary endpoint (33.3% vs 9.6%, p = 0.034) and more patients underwent urgent HT (13.3% vs 1.4%, p = 0.44). RV-arterial coupling was associated with a lower survival free of events during follow-up (log-rank p = 0.010). Conclusion: RV-arterial coupling predicts a worse prognosis in advanced HF patients, with those below a cutoff of 0.36 mm/mmHg having lower survival. This variable may improve risk stratification in this setting.